AutoCAD Practicum Teaching Strategies and Systems Using the Team Viewer Application - Hilmy, Zakwan; Khairiyah, Karunia Yulinda; Dasira, Alyuan; Prawira, Muhammad Zaki; Shakri, Muhammad (Jurnal Ilmiah Pendidikan dan Pembelajaran, 2023)
After COVID-19 pandemic era, the online teaching process has been adapted and used for various learning purposes. Some of the shortcomings of the online system are the limited interaction in practical learning, such as application-based practice. In addition, the process of practicum is not optimal because some students cannot carry out the instructions given due to the limited equipment of the students such as personal computers or laptops. Therefore, this research was conducted to make modifications to the application-based practicum system (AutoCAD practicum) with a remote system using the Team Viewer application. This study uses mixed method qualitative and quantitative where the questionnaire was given to participants after the training. The population that will be used in this study are all students who take the Introduction to Design engineering course with AutoCAD Practicum material. The results of this study show that the accessibility, interface and operation of the AutoCAD application can be done properly using the Team Viewer application with the students' smartphone media so that the practicum can be done properly. This strategy can overcome the problems of limited equipment and passive interaction during the practicum process. In addition, the strategies and methods can be widely applied to learning in general and other application-based practicums.